Coronary periarteritis and pericarditis are rare but distinct manifestations of heart involvement in IgG4-related disease: a retrospective cohort study - Hua, Tianrui; Du, Juan; Guo, Xiaoxiao; Peng, Linyi; Zhou, Jiaxin; Nie, Yuxue; Man, Dafu; Li, Mengtao; Pan, Lili; Zhang, Wen (Orphanet journal of rare diseases, 2024)
The heart can be involved in immunoglobulin (Ig)-G4-related disease (IgG4-RD). This study aimed to summarize the clinical features and efficacy of treatment for IgG4-RD patients with heart involvement. We conducted a retrospective study enrolling 42 IgG4-RD patients with heart involvement from the IgG4-RD cohorts of the Peking Union Medical College Hospital and Beijing An Zhen Hospital, from 2010 to 2022. Clinical, laboratory, radiological data were collected, and treatment responses to glucocorticoids and immunosuppressants were analyzed. IgG4-related cardiac involvement is a rare part of the IgG4-RD spectrum. The incidences of coronary periarteritis and pericarditis were 1.2%(13/1075) and 3.1%(33/1075), respectively in our cohort. Valvular disease possibly related to IgG4-RD was detected in two patients. None of the patients with myocardial involvement were identified. The average age was 58.2 ± 12.8 years, with a male predominance (76.7%). Coronary artery CT revealed that mass-like and diffuse wall-thickening lesions were the most frequently observed type of coronary periarteritis. Pericarditis presented as pericardial effusion, localized thickening, calcification and mass. After treatment with glucocorticoid and immunosuppressants, all patients achieved a reduced IgG4-RD responder index score and achieved radiological remission. Two patients with coronary peri-arteritis experienced clinical relapses during the maintenance period. Cardiac involvement in IgG4-RD is rare and easily overlooked since many patients are asymptomatic, and the diagnosis relies on imaging. Patients showed a satisfactory response to glucocorticoid based treatment.